The challenges faced by small and medium enterprises in accessing credit in Namibia - Amadhila, Beatus (Graduate School of Business (GSB), 2021)
This study sets out to explore the challenges associated with small and medium enterprises (SME) in obtaining funds from financial institutions. Specifically, it seeks to identify the types of credit facilities used by SMEs in Namibia, examine the factors that limit SME access to credit from banks and to understand the challenges associated with SMEs in accessing credit facilities. This study employs the logistic technique to correlate survey data from 120 small and medium firms in Namibia, to examine the likelihood of access to credit from a financial institution. The study has found that the type of credit used by SMEs is either short-term loans, medium-term loans or long-term loans. The conclusion reached is that the majority of SME business owners preferred short-term loans to finance their business activities. This leads to another question: whether financial institutions' products, designed for the SME sector, are well aligned with this finding or if this is another challenge to SMEs in accessing funds. The study revealed factors in accessing credit by small and medium-sized enterprises, including: requests by the financial institutions for collateral and audited financial statements of account; length of operation, and details of competent management, capable of giving the banks confidence and assuring them that the loans will be repaid; rates of interest which determine the loan costs. These are some of the factors that determine SME access to finance. The study strongly recommends that SME businesses keep up-to-date business financial records for various reasons, such as to keep track of their operations, and to provide this information to financial institutions in the event of their making applications for funding. Also, SME firms should build strong balance sheets, displaying their profits, so as to ensure that they are able to meet the collateral requirements of the financial institutions.